Undifferentiated carcinoma with osteoclast-like giant cells of the ampullary region: Short term survival after pancreaticoduodenectomy. (2016) - Kawamoto, Yusuke; Ome, Yusuke; Terada, Kazuhiro; Hashida, Kazuki; Kawamoto, Kazuyuki; Ito, Tadashi
Highlights: A rare case of undifferentiated carcinomas with osteoclast-like giant cells of the ampullary region successfully treated with pancreaticoduodenectomy. Carcinoma in situ was also observed, spreading from the tumor at the terminal segment of the common bile duct to the surgical margin of the common hepatic duct. It is important to intraoperatively confirm negative bile duct margins by rapid pathologic diagnosis. Abstract: Introduction: Undifferentiated carcinomas with osteoclast-like giant cells (UC-OGCs) of the ampullary region are very rare, with only a few cases reported to date. The clinicopathological features, treatment options, and prognosis of UC-OGCs are unclear. This report describes a patient with UC-OGCs of the ampullary region. Presentation of case: A 78-year-old male patient was admitted for epigastric pain and fever. Contrast-enhanced computed tomography revealed a 2.6-cm mass at the duodenal papilla. Duodenoscopy revealed a smooth red protruding mass compressing the orifice of the papilla of Vater. Biopsy of the mass showed proliferation of osteoclast-like giant cells. A subtotal stomach-preserving pancreaticoduodenectomy was performed, and the tumor was histologically diagnosed as an UC-OGCs of the ampullary region. Carcinoma in situ was also observed, spreading from the tumor at the terminal segment of the common bile duct to the common hepatic duct, with carcinoma cells at the surgical margin of the common hepatic duct. One year after surgery, the patient is alive and without tumor recurrence. Discussion: UC-OGCs of the ampullary region is very rare neoplasm containing osteoclast-like giant cells and mononuclear cells. Osteoclast-like giant cells may originate from reactive mesenchymal cells and carcinoma in situ may spread to the common hepatic duct. Surgery including pancreaticoduodenectomy may be a treatment option for resectable tumors, whereas gemcitabine may be a treatment option for unresectable tumors. Conclusion: Carcinoma in situ may spread quite far (5 cm) to the common hepatic duct, making it desirable to intraoperatively confirm negative bile duct margins by rapid pathologic diagnosis.